Limited Impact of Serial Follow-Up Imaging in Clinically Stable Patients With Brainstem Cavernous Malformations - Velz, Julia; Vasella, Flavio; Yang, Yang; Neidert, Marian Christoph; Regli, Luca; Bozinov, Oliver (Frontiers in Neurology, 2020)
Background: Clinical management of patients with brainstem cavernous malformations (BSCM) is often challenging due to the unpredictable clinical course and lack of high-quality evidence. Nevertheless, radiologic follow-up is often performed routinely. The objective of this work was to investigate whether active follow-up by serial imaging is justified and how planned imaging will impact clinical decision making in absence of clinical progression. Methods: We included all consecutive patients with BSCM treated and followed at our Department between 2006-2018. Results: Of 429 patients with CCM, 118 were diagnosed with BSCM (27.5%). Patients were followed for a mean of 8.1 (± 7.4 SD) years. Conservative treatment was recommended in 54 patients over the complete follow-up period, whereas 64 patients underwent surgical extirpation of BSCM. In total, 75 surgical procedures were performed. Over a period of 961 follow-up years in total, routinely performed follow-up MRI in clinically stable patients did not lead to a single indication for surgery. Conclusion: Due to the difficult-to-predict clinical course of patients with BSCM and the relatively high risk associated with surgery, routine imaging is unlikely to have any influence on surgical decision making in clinically stable patients with BSCM.